Remarks on architecture the Vitruvian tradition in enlightenment Poland - Potocki, Ignacy 1750-1809 (Penn State Univ. Press, 2015)
At the end of the eighteenth century, the authors of Polands 3 May 1791 Constitution became the heirs to a defunct state whose territory had been partitioned by Russia, Prussia, and Austria. At this moment of intensive national postmortem, Ignacy Potocki, an eminent statesman and co-author of the Constitution, composed an architectural treatise. One of the best-preserved examples of early modern Polish architectural thought, published and translated here for the first time, the Remarks on Architecture announces itself as a project of national introspection, with architecture playing a direct role in the betterment of the nation. In it, Potocki addresses his remarks to the contemporary Polish nobility and conveys the lessons of a Vitruvian canon that shaped Continental classical architectural theory and practice throughout the early modern period. He argues that architecture is a vessel for cultural values and that it plays an important part in the formation and critique of broader national traditions. In her introduction, Carolyn Guile further explores Polish Enlightenment architectural writing as an example of cultural exchange, inheritance, and transformation. This is a work that broadens our understanding of European architectural history during the early modern period